LAMOST Young Stellar Objects. I. Spectroscopically Identifying and Characterizing M-type YSOs - Xiang-Song Fang; Jian-Rong Shi; Ming-Yi Ding; Zi-Huang Cao (The Astrophysical Journal)
This study utilized Large sky Area Multi-Object fiber Spectroscopic Telescope (LAMOST) low-resolution spectra to identify M-type young stellar objects (YSOs) and characterize their accretion signatures. We measured characteristic features, including hydrogen Balmer, Li i , He i , Na i , and Ca ii lines, as well as molecular absorption bands such as CaH. These features were evaluated for their potential to distinguish between different classes of M-type stars. In addition to the commonly used H α emission and Li i λ 6708 absorption, other features such as He i , Na i , Ca ii HK and infrared triplet (IRT) lines, and CN, CaH, and VO bands also show potential for identifying YSOs from M-type dwarfs and giants. Based on key red-band features, we identified over 8500 M-type YSO candidates from the LAMOST DR8 archive using the random forest technique, with over 2300 of them likely being classical T Tauri stars (CTTSs). By incorporating Gaia astrometry, Two Micron All Sky Survey photometry, and extinction from 3D dust maps, we estimated the basic properties (such as age and mass) of the YSO candidates based on parsec models. We also estimated the mass accretion rates of the CTTS candidates using H α emission. The derived accretion rates show a dependence on age and mass similar to that described in previous studies. Significant scatter in mass accretion rates exists even among stars with a similar age and mass, which may be partly attributed to variations in H α emission and the veiling.